2002
DOI: 10.1046/j.1365-2133.2002.04839.x
|View full text |Cite
|
Sign up to set email alerts
|

A case of Sezary's syndrome associated with granulomatous lesions, myelodysplastic syndrome and transformation into CD30-positive large-cell pleomorphic lymphoma

Abstract: Sézary's syndrome (SS) is a leukaemic variant of mycosis fungoides, a cutaneous T-cell lymphoma showing distinct clinical, histological, immunological, and genotypic features. We report a 10-year follow-up of a patient with SS exhibiting unusual features such as granulomatous skin lesions, transformation to a CD30-positive large-cell pleomorphic T-cell lymphoma, and development of myelodysplastic syndrome and review the cases of SS reported in the literature with these unusual and rare complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
(72 reference statements)
1
21
0
Order By: Relevance
“…2 In addition, the incidence of large cell transformation in MF and less often in SS is a well known phenomenon, having been reported in 8% to 55% of cases. [11][12][13][14] However, to our knowledge, the transition of SS into MF has not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…2 In addition, the incidence of large cell transformation in MF and less often in SS is a well known phenomenon, having been reported in 8% to 55% of cases. [11][12][13][14] However, to our knowledge, the transition of SS into MF has not been reported yet.…”
Section: Resultsmentioning
confidence: 99%
“…7,8,10,23,24,27,28,32,33,34,36 Granulomatous infiltration has recently been reported in a subset of cutaneous lymphoproliferative disorders with dual lineage rearrangement. 18 Some of these patients also evidenced large binucleated cells raising the differential diagnosis of Hodgkin disease.…”
Section: Disscusionmentioning
confidence: 99%
“…Median time from diagnosis of MF to transformation was found to be 6.5 years, and the survival from transformation to death was 22 months. 15,16 Molecular studies based on T-cell receptor analysis have demonstrated that the large-cell infiltrate in transformed MF/Sézary syndrome represents evolution from the original malignant clone. 7 In Sézary syndrome, transformation clinically manifests with large tumors, which may ulcerate.…”
Section: Discussionmentioning
confidence: 99%